1980
DOI: 10.1002/bms.1200071007
|View full text |Cite
|
Sign up to set email alerts
|

Studies on anabolic steroids. The mass spectra of 17α-methyl-17β-hydroxy-1,4-androstadien-3-one (dianabol) and its metabolites

Abstract: The metabolism of 17 alpha-methyl-17 beta-hydroxy-1,4-androstadien-3-one (dianabol) in human adults has been studied in detail by computer aided capillary gas chromatography mass spectrometry. After oral administration to man six metabolites were determined in the free fraction of the urine samples, the structures of which have been identified as 17-epidianabol, three isomers of 6-hydroxydianabol, 17 alpha-methyl-17 beta-hydroxy-1,4,6-androstatrien-3-one (delta 6-dianabol) and 18-nor-17,17-dimethyl-1,4,13(14)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Other major unconjugated metabolites subsequently identi¢ed were the 17a-hydroxy epimer of methandienone (17-epimethandienone) and the 6b-hydroxylated metabolite of epimethandienone. 84,86 In the conjugate fraction of urine, three major bishydroxylated metabolites (5b-H orientation) have been identi¢ed; 88 these steroids have a 3a-hydroxyl group which facilitates conjugation to glucuronic acid in the human. A fourth metabolite has a 1-ene-3-oxo con¢guration but has also been found in the conjugate fraction, 88 presumably because of formation of a 3-hydroxyl group by keto-enol tautomerism, which can then be conjugated with uridine diphosphoglucuronic acid.…”
Section: Metabolism Of Nandrolonementioning
confidence: 99%
“…Other major unconjugated metabolites subsequently identi¢ed were the 17a-hydroxy epimer of methandienone (17-epimethandienone) and the 6b-hydroxylated metabolite of epimethandienone. 84,86 In the conjugate fraction of urine, three major bishydroxylated metabolites (5b-H orientation) have been identi¢ed; 88 these steroids have a 3a-hydroxyl group which facilitates conjugation to glucuronic acid in the human. A fourth metabolite has a 1-ene-3-oxo con¢guration but has also been found in the conjugate fraction, 88 presumably because of formation of a 3-hydroxyl group by keto-enol tautomerism, which can then be conjugated with uridine diphosphoglucuronic acid.…”
Section: Metabolism Of Nandrolonementioning
confidence: 99%
“…[7][8][9][10][11][12][13] The metabolism of metandienone has been investigated in detail providing the basis for all commonly accepted and employed screening and confirmation procedures for this particular drug in doping controls 8,14-16 using gas chromatography (GC) interfaced to low-or high-resolution mass spectrometry (MS). Major metabolites being used as target analytes in screening assays are 17a-methyl-5a-androstane-3a,17b-diol, 17a-methyl-5b-androstane-3a,17b-diol, 17b-methyl-5b-androst-1-ene-3a,17a-diol (epimetendiol) and 18-nor-17,17-dimethyl-5b-androst-1,13-dien-3a-ol (18-norepimetendiol) (Scheme 1, 3-6), 7,17,18 the latter two of which have allowed long-term detection of metandienone abuse after cessation. Due to the low proton affinity of these compounds, the use of GC/MS after derivatization of target compounds has been preferred over soft ionization techniques such as electrospray ionization (ESI) or atmospheric pressure chemical ionization (APCI) to identify their presence in doping control specimens.…”
mentioning
confidence: 99%
“…1). It has previously been reported that epimerization can lead to different metabolites through an intermediate sulfate conjugate (21,22,24,25,32,33 ). The 17␤-sulfate hydrolyzes in water to several products, including metabolites III and VI.…”
Section: 17-dimethyl-18-norandrosta-1413-trien-3-one (Metabolitementioning
confidence: 99%
“…Three of the 4 detected peaks could be related to compounds previously reported. The most abundant peak (VIIa) can be associated with 17␣-methyl-17␤-hydroxyandrosta-1,4,6-trien-3-one (6-enemethandienone) (22,24,34 ). Two other peaks could be assigned to metabolite VII itself (17 ) and the 17-epimer of VII (VIIc) (27 ), by comparison to authentic reference standards.…”
Section: Trien-3-one (Metabolite Vii)mentioning
confidence: 99%
See 1 more Smart Citation